Phenomenological Study: The Role Of The Financial Services Authority In Resolving Islamic Banking Customer Problems - Masdaliana Putri Assalam; Jelita Jelita; Haidi Hajar Widagdo (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Problems in the banking world often make customers as disadvantaged parties both materially and immaterially. This certainly encourages customers to make efforts that can avoid losses both in litigation and non-litigation. The purpose of this study is to determine the role of the financial services authority in solving problems experienced by Islamic bank customers. The method used in this study is a qualitative method with a phenomenological approach. Phenomenological studies with data collection methods, namely by observation and interviews. The results of this study show that the financial services authority has an important role in solving customer problems and customer legal protection. The manifestation of the role of the financial services authority can be seen from its authority in terms of taking actions both legally and reprimands to the banking industry to respond and resolve Problems experienced by customers, in addition to their authority in terms of filing claims for compensation or return of customer assets lost due to the bank's fault.